The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jdv.16189
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum vitamin D level and risk and prognosis of melanoma: a systematic review and meta‐analysis

Abstract: Background Vitamin D has antineoplastic effects, but the synthesis of vitamin D requires ultraviolet radiation, a known risk factor for melanoma. Objective To investigate the correlations between serum vitamin D levels and risk and prognosis of melanoma. Methods A systematic review and meta-analysis were conducted. Online databases were searched on 31 Oct 2018. Results Twenty-five studies with a total of 11166 patients with melanoma were included. There was no significant difference in serum vitamin D levels b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
2
23
1
Order By: Relevance
“…Nevertheless, anti-proliferative and pro-apoptotic properties of vitamin D have indeed been demonstrated in animal and in vitro studies 94,95 , and 1,25(OH)D has been shown to regulate multiple signaling pathways involved in differentiation, inflammation, invasion, angiogenesis and metastasis 17 . Recently, a pooled analysis of 25 studies showed that lower vitamin D levels were associated with higher Breslow thickness and mortality rates in patients with melanoma 96 . Several studies suggested that higher vitamin D levels may confer better prognosis from melanoma including Breslow thickness 30,97 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, anti-proliferative and pro-apoptotic properties of vitamin D have indeed been demonstrated in animal and in vitro studies 94,95 , and 1,25(OH)D has been shown to regulate multiple signaling pathways involved in differentiation, inflammation, invasion, angiogenesis and metastasis 17 . Recently, a pooled analysis of 25 studies showed that lower vitamin D levels were associated with higher Breslow thickness and mortality rates in patients with melanoma 96 . Several studies suggested that higher vitamin D levels may confer better prognosis from melanoma including Breslow thickness 30,97 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies suggest that vitamin D limits invasion and angiogenesis of tumour cells. Furthermore, VDR genetic mutations correlate with an increased risk to incur in melanoma and with a graver prognosis 21,22 . www.nature.com/scientificreports/ Finally, the trend that emerges in this study recognizes lower VDSL in association with negative prognostic factors and advanced stage neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, vitamin D insufficiency (21-29 ng/mL) versus deficiency (≤20 ng/mL) was found to be significantly inversely associated with melanoma (OR = 0.13, 0.06-0.27, p < 0.001), suggesting that the more vitamin D approaches normal values, the lower the OR, and the greater the protective action. Moreover, in a pooled analysis of 25 studies, 25(OH)vit D levels showed an inverse association with Breslow thickness (Standardized Mean Difference (SMD) = 0.24, 0.16-0.33, p < 0.001 for ≤1 vs. >1 mm thickness) and mortality rates in melanoma patients (HR = 1.56, 1.26-1.93, p < 0.001) [101].…”
Section: Vitamin Dmentioning
confidence: 98%